1975
DOI: 10.1056/nejm197501302920504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corticosteroid Therapy on Human Monocyte Function

Abstract: Since high-dose corticosteroid therapy appears to impair cellular defense mechanisms, this study examined its effect on human monocyte function. Fifteen normal volunteers were studied before and after a three-day course of prednisone therapy (50 mg every 12 hours for six doses). A transient period of monocytopenia occurred during the first few hours of therapy. Monocyte killing of Staphylococcus aureus was reduced in nine subjects from 5.6 plus or minus 0.2 (plus or minus S.E.) X 10-6 organisms before to 1.3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
2
3

Year Published

1978
1978
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(78 citation statements)
references
References 21 publications
3
70
2
3
Order By: Relevance
“…None of them had been treated by either inhaled or oral GC for the past 3 months. 2 agonists were used as needed by the asthma symptoms. Six healthy volunteers were also included in this study; they were age-(25-45 years (35 6 5 years)) and sex-(3M/3F) matched.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of them had been treated by either inhaled or oral GC for the past 3 months. 2 agonists were used as needed by the asthma symptoms. Six healthy volunteers were also included in this study; they were age-(25-45 years (35 6 5 years)) and sex-(3M/3F) matched.…”
Section: Patientsmentioning
confidence: 99%
“…Several studies have shown a decrease of cellular infiltration into asthmatic airways following treatment with glucocorticoids (GC) [2]. Generally, GC are able to interfere with the in vivo production of inflammatory mediators to suppress the putative in vivo inflammatory response [3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, after in vivo or in vitro exposures to GCs, bactericidal and fungicidal ability (Rinehart et al, 1975), cytokine production, MHC class II expression (Snyder and Unanue, 1982) and tumoricidal activity (Hogan and Vogel, 1988;Keil et al, 1995) of humans and murine macrophages were decreased. In vivo, high levels of plasma cortisol produced by stressors can lead to divergent responses including a strong immunosuppressive eVect (Cupps and Fauci, 1982;Rinehart et al, 1975). In Wsh, cortisol (hydrocortisone) is the major corticosteroid with both GC and MC activities.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The dynamics of marrow adipocytes under conditions of corticosteroid administration should be viewed in terms of this differentiation-apoptosis balance 23 and also from the viewpoint of phagocytotic activity. [24][25][26] Regardless of the source of fat globules, we postulated a process of arteriole occlusion once fat globules are formed in the arterial system. The fat globules may initially be very small in size, but can coalesce with ease and become larger.…”
Section: Discussionmentioning
confidence: 99%